Implication of noticing and changing nomophobia: the perspective of university students with high and moderate nomophobia in Malaysia - Pang, Khong Yun; Ooi, Pei Boon; Tan, Yee Kee; Siau, Ching Sin; Chan, Caryn Mei Hsien; Lai, Samantha Arielle; Sulong, Rose Manisah; Ho, Meng Chuan (Global Academic Excellence, 2023)
Anticipating the increasing usage of mobile phones and the internet, nomophobia emerges as a modern psychological condition for those who manifest fear in the absence of phones and the internet. The global prevalence and correlational studies have unveiled the severity of the nomophobic condition and call for the need for future research. The objectives of this study are to explore the awareness of nomophobia and the intention to change nomophobia among university students. This study will also help to establish the reception of nomophobia-based intervention among university students and the role of religion to alleviate the symptoms of nomophobia. Using purposive sampling, 15 semi-structured interviews were conducted through an online medium. Four themes were identified: 1) awareness of nomophobia, 2) thoughts on nomophobia intervention, 3) religion and nomophobia, and 4) the intention to change nomophobia. The findings indicate that there is a need to raise awareness of nomophobia, while the intention to change phone usage is guided by aspects that are outlined in the health belief model and the theory of planned behaviour. University students were found to generally perceive nomophobia intervention and religious practices positively in helping to overcome nomophobia.